Persons with reduced mobility and consequences related to their demand for public passenger transport in the conditions of Slovak Republic - Vladimír Konečný; Martin Zuzaniak; Dominika Jonasíková; Borna Abramović (Transportation Research Interdisciplinary Perspectives)
In the tariff conditions and fare lists of public passenger transport in the Slovak Republic, there are also groups of passengers who are holders of disability/disability with companion cards and their companions. This group of passengers is transported at discounted or free fares, the level of fares for card holders and discounts to the full fare is individual to the specific transport system. One of the reasons for our research was the identified significant average annual increase in the number of card holders for disabled persons11 PWD – Person with disability. (PWD) – 6,22% and disabled persons with a companion22 PWD-C − Person with disability with a companion (PWD-C) – 5,1% in the Slovak Republic between the years 2013 and 2022. Geographically, single-criterion regression models of the dependence of the number of cards on the population were set up for the regions in the Slovak Republic, where the coefficients of determination reach significant values. A cluster analysis of all 79 districts was also performed, which identified eight differently sized clusters of districts in the SR. Within each cluster, the same or similar fare conditions and fares could be applied in public passenger transport for the group of PWD and PWD-C. A synthetic indicator has also been proposed as part of the research on the issue, which will be validated in further follow-up research on the impact of the individual sub-factors on the number of disability cards (DC) and a disability-with a companion cards (DWCC) in the identified clusters of districts. The influence rate of the sub-factors in each cluster of districts was verified.